QAM modem for wireless application / Hafizah Abdullah - Abdullah, Hafizah (2001)
This project covers two parts. The first part of the project is obtaining the QAM constellation diagram in clear channel and noisy channel. The second part simulate three types of transmission channel; Gaussian, Rayleigh and Rician. The objective is to study bit error rate, symbol error rate, channel characteristic and signal speed. The simulation was done using Matlab.